2023
DOI: 10.3390/foods12183417
|View full text |Cite
|
Sign up to set email alerts
|

The Antioxidant Activities In Vitro and In Vivo and Extraction Conditions Optimization of Defatted Walnut Kernel Extract

Xiaomei Zhou,
Xiaojian Gong,
Xu Li
et al.

Abstract: The objective of this study was to determine the antioxidant activities of defatted walnut kernel extract (DWE) and whole walnut kernel extract (WE) in vitro and in vivo. Three spectrophotometric methods, DPPH, ABTS, and FRAP, were used in in vitro experiments, and mice were used in in vivo experiments. In addition, response surface methodology (RSM) was used to optimize reflux-assisted ethanol extraction of DWE for maximum antioxidant activity and total phenolic content. The results of in vitro experiments sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…[10]. Zhao et al [11] showed that walnut kernel extract could increase the activity of antioxidant enzymes and reduce lipid peroxidation products in the serum and tissues of mice. Tocopherol exhibits numerous beneficial properties, such as contributing to reducing the risk of coronary heart disease [12] and having anti-inflammatory and anti-proliferative effects in cancer [13].…”
Section: Introductionmentioning
confidence: 99%
“…[10]. Zhao et al [11] showed that walnut kernel extract could increase the activity of antioxidant enzymes and reduce lipid peroxidation products in the serum and tissues of mice. Tocopherol exhibits numerous beneficial properties, such as contributing to reducing the risk of coronary heart disease [12] and having anti-inflammatory and anti-proliferative effects in cancer [13].…”
Section: Introductionmentioning
confidence: 99%